(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This Study Aimed To Identify The Relationship Between Intellectual Capital And Organizational Performance By Clarifying The Impact Of Intellectual Capital In Its Dimensions (Human Capital, Structural Capital, Relational Capital) On The Organizational Performance Of Food Industry Organizations Operating In Damascus Governorate. The Researcher Used The Descriptive Approach As It Describes The Studied Phenomenon As It Is In Reality, By Distributing 75 Questionnaires To A Random Sample Of Administrative Workers In Food Industry Organizations Operating In Damascus Governorate. The Number Of Questionnaires Suitable For Statistical Analysis Was (61), With A Percentage Of (81%). One Of The Most Important Results Reached Was: There Is A Positive Impact Of The Dimensions Of Intellectual Capital On The Organizational Performance Of The Food Industry Organizations Under Study, As The Most Influential Dimension Was Human Capital, Followed By Structural Capital, Then Relational Capital. Among The Most Important Proposals Of This Study: The Need For Food Industry Organizations In Damascus Governorate To Adopt A Strategy To Re-Engineer Human Resources By Developing Work Philosophy, And Preserving Human Resources And Competencies By Providing Material And Moral Incentives To Improve Performance, In Addition To Reconsidering The Organizational Structure Of These Organizations In A Way That Is Compatible With The Era. Knowledge In Order To Achieve Efficiency And Effectiveness Of Performance.